1987
DOI: 10.1128/jb.169.9.4279-4284.1987
|View full text |Cite
|
Sign up to set email alerts
|

Mutations that create new promoters suppress the sigma 54 dependence of glnA transcription in Escherichia coli

Abstract: Escherichia coli rpoN mutants lack or4 and are therefore unable to initiate the transcription of ginA at glnAp2, which is required for the production of a high intracellular concentration of glutamine synthetase. We have found that the dependence on a54 can be overcome by iutations that have apparently created a new r70-dependent promoter. The position -35 RNA polymerase contact site of this new promoter overlaps glnAp2.The initiation of transcription at the new promoter is inhibited by r54-RNA polymerase even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 24 publications
(60 reference statements)
1
29
1
Order By: Relevance
“…The active fraction was eluted at a KCl concentration of approximately 0.25 M, and concentrated to about 10 ml on a Amicon UM-10 membrane. The concentrated enzyme was dialyzed against buffer C (the buffer B containing 10mM (CH 3 COOhMg), and then applied to a Blue-Cellulofine column (2.5 x 20 cm) equilibrated with buffer C. The.column was washed with 0.1 M KCl in buffer C, and the enzyme was then eluted with a linear gradient from 0.1 MKCl, 10 mM (CH 3 COOhMg to 1.0 M KCl, 0 mM (CH 3 COOhMg in buffer C. The active fraction was concentrated on the Amicon membrane and dialyzed against buffer B. The puriffed enzyme could be stored at -70°C without loss of activity for at least one month.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The active fraction was eluted at a KCl concentration of approximately 0.25 M, and concentrated to about 10 ml on a Amicon UM-10 membrane. The concentrated enzyme was dialyzed against buffer C (the buffer B containing 10mM (CH 3 COOhMg), and then applied to a Blue-Cellulofine column (2.5 x 20 cm) equilibrated with buffer C. The.column was washed with 0.1 M KCl in buffer C, and the enzyme was then eluted with a linear gradient from 0.1 MKCl, 10 mM (CH 3 COOhMg to 1.0 M KCl, 0 mM (CH 3 COOhMg in buffer C. The active fraction was concentrated on the Amicon membrane and dialyzed against buffer B. The puriffed enzyme could be stored at -70°C without loss of activity for at least one month.…”
Section: Resultsmentioning
confidence: 99%
“…A nucleotide sequence derived from pKK223-3 was underlined with a double line. (CH 3 COOhMg, 1mM EDTA, 30mM KCl, and 5mM 2-mercaptoethanol) and re-collected by centrifugation. The cells were then suspended in 50 ml of buffer A and disrupted by sonication at O°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, asparagine synthetase using glutamine as amido nitrogen donor [Laspartate: L-glutamine amido-ligase (AMP-forming) E.C. 6.3.5.4] is found not only in prokaryotes (Humbert & Simoni, 1980;Reitzer & Magasanik, 1982) but also in eukaryotes (Andrulis, Chen & Ray, 1987;Gantt & Arfin, 1981;Hongo & Sato, 1981 ;, and encoded by the asnB gene. Studies of steady-state kinetic mechanisms for both enzymes have demonstrated that the mechanism of the ammonia-dependent enzymes is different from that of the glutamine-dependent enzymes (Cedar & Schwartz, 1969b;Hongo & Sato, 1985;Mehlhaff, Luehr & Schuster, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…6.3.1.1] catalyzes the synthesis of L-asparagine from L-aspartate and ammonia, with hydrolyzing ATP to AMP and PPi (Meister, 1974). This enzyme is distributed in prokaryotes as Escherichia coli (Cedar & Schwartz, 1969a) and Klebsiella aerogenes (Reitzer & Magasanik, 1982), and encoded by the asnA gene. On the other hand, asparagine synthetase using glutamine as amido nitrogen donor [Laspartate: L-glutamine amido-ligase (AMP-forming) E.C.…”
Section: Introductionmentioning
confidence: 99%